ma351 solution mannul

# ma351 solution mannul - Section 1.1 Chapter 1 Section 1.1...

This preview shows pages 1–3. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Section 1.1 Chapter 1 Section 1.1 1.1. 1 bracketleftbigg x + 2 y = 1 2 x + 3 y = 1 bracketrightbigg − 2 × 1st equation → bracketleftbigg x + 2 y = 1 − y = − 1 bracketrightbigg ÷ ( − 1) → bracketleftbigg x + 2 y = 1 y = 1 bracketrightbigg − 2 × 2nd equation → bracketleftbigg x = − 1 y = 1 bracketrightbigg , so that ( x,y ) = ( − 1 , 1). 1.1. 3 bracketleftbigg 2 x + 4 y = 3 3 x + 6 y = 2 bracketrightbigg ÷ 2 → bracketleftbigg x + 2 y = 3 2 3 x + 6 y = 2 bracketrightbigg − 3 × 1st equation → bracketleftbigg x + 2 y = 3 2 = − 5 2 bracketrightbigg . So there is no solution. 1.1. 5 bracketleftbigg 2 x + 3 y = 0 4 x + 5 y = 0 bracketrightbigg ÷ 2 → bracketleftbigg x + 3 2 y = 0 4 x + 5 y = 0 bracketrightbigg − 4 × 1st equation → bracketleftbigg x + 3 2 y = 0 − y = 0 bracketrightbigg ÷ ( − 1) → bracketleftbigg x + 3 2 y = 0 y = 0 bracketrightbigg − 3 2 × 2nd equation → bracketleftbigg x = 0 y = 0 bracketrightbigg , so that ( x,y ) = (0 , 0). 1.1. 7 x + 2 y + 3 z = 1 x + 3 y + 4 z = 3 x + 4 y + 5 z = 4 − I − I → x + 2 y + 3 z = 1 y + z = 2 2 y + 2 z = 3 − 2( II ) − 2( II ) → x + z = − 3 y + z = 2 = − 1 This system has no solution. 1.1. 9 x + 2 y + 3 z = 1 3 x + 2 y + z = 1 7 x + 2 y − 3 z = 1 − 3( I ) − 7( I ) → x + 2 y + 3 z = 1 − 4 y − 8 z = − 2 − 12 y − 24 z = − 6 ÷ ( − 4) → x + 2 y + 3 z = 1 y + 2 z = 1 2 − 12 y − 24 z = − 6 − 2( II ) +12( II ) → x − z = 0 y + 2 z = 1 2 = 0 This system has infinitely many solutions: if we choose z = t , an arbitrary real number, then we get x = z = t and y = 1 2 − 2 z = 1 2 − 2 t . Therefore, the general solution is ( x,y,z ) = ( t, 1 2 − 2 t,t ) , where t is an arbitrary real number. 1.1. 11 bracketleftbigg x − 2 y = 2 3 x + 5 y = 17 bracketrightbigg − 3( I ) → bracketleftbigg x − 2 y = 2 11 y = 11 bracketrightbigg ÷ 11 → bracketleftbigg x − 2 y = 2 y = 1 bracketrightbigg +2( II ) → bracketleftbigg x = 4 y = 1 bracketrightbigg , so that ( x,y ) = (4 , 1). See Figure 1.1. 1.1. 13 bracketleftbigg x − 2 y = 3 2 x − 4 y = 8 bracketrightbigg − 2( I ) → bracketleftbigg x − 2 y = 3 = 2 bracketrightbigg , which has no solutions. (See Figure 1.2.) 1.1. 15 The system reduces to x = 0 y = 0 z = 0 so the unique solution is ( x,y,z ) = (0 , , 0). The three planes intersect at the origin. 1 Chapter 1 Figure 1.1: for Problem 1.1.11. Figure 1.2: for Problem 1.1.13. 1.1. 17 bracketleftbigg x + 2 y = a 3 x + 5 y = b bracketrightbigg − 3( I ) → bracketleftbigg x + 2 y = a − y = − 3 a + b bracketrightbigg ÷ ( − 1) → bracketleftbigg x + 2 y = a y = 3 a − b bracketrightbigg − 2( II ) bracketleftbigg x = − 5 a + 2 b y = 3 a − b bracketrightbigg , so that ( x,y ) = ( − 5 a + 2 b, 3 a − b )....
View Full Document

{[ snackBarMessage ]}

### Page1 / 112

ma351 solution mannul - Section 1.1 Chapter 1 Section 1.1...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online